Spatio-temporal distribution of Neomegalotomus parvus (Hemiptera: Alydidae) in soybean/corn crop with beetle bank - Fernandes Martins, Ivan Carlos; Cividanes, Francisco Jorge [UNESP]; Barbosa, Jose Carlos [UNESP]; Panizzi, AntOnio Ricardo; Lima Junior, Joaquim Alves; Campos, Lourival Dias (Univ Federal Rural Pernambuco, 2020)
The true bug Neomegalotomus parvus (Westwood) is known as an insect pest of some agricultural crops. However, is limited information on the behavior and influence of environmental factors on its occurrence in the field. This study aimed to determine the population dynamics and spatial distribution of N. parvus in soybean and corn crops with presence of a refuge area. Conducted this study in an area with soybean/corn crop succession, and with fallow period both where there was a beetle bank, to assess the spatial distribution pattern of N. parvus and to link their eventual aggregation and colonization to the presence of a beetle bank. We also evaluated the influence of rainfall, air temperature and the phenological stages of the crops on the temporal distribution of this true bug. The results showed that N. parvus has an aggregated pattern of spatial distribution and that aggregation and colonization is related to the agricultural field but does not benefit from the presence of the beetle bank. The higher abundance of N. parvus occurred during the corn crop period when the grains were physiologically mature and when there was reduced rainfall and milder temperatures. These results may contribute to the development of a management plan for N. parvus, where actions could be directed.
Keywords: aggregate distribution; phenological phases; refuge areas; true bug